URGENSI PENGATURAN PEREDARAN MINUMAN BERALKOHOL MELALUI PERATURAN DAERAH DI KOTA SALATIGA - FX. Joko Priyono (Faculty of Law, Universitas Diponegoro, 2014)
The Salatiga Regional Government has been facing “extraordinary condition” due to alcohol circulation problem. Some people has been victims for drinking “mixture drink” during 5 years. The government can't uphold the law because of no validity of it. The Regional Government Regulation No. 15 of 1998 can't not be legal basis. The Law was based on Presidential Decree Number 3 of 1997 which was then annulted by the Supreme Court Decision No. 42 P/HUM/2012 dated June 18, 2013. It is, therefore, necessary to issue Government Regulation of controlling and supervising alcohol drink to prevent and punish illegal alcohol drink circulation